Studi Etnomatematika: Konstruksi Bangun Ruang Sisi Lengkung pada Pembuatan Gerabah di Desa Banyumulek - Laylatul Hidayah (Jurnal Tadris Matematika, 2022)
This study was motivated by the observation that students who understand formal mathematics do not necessarily understand non-formal mathematics in society. This shows that mathematics learning in schools has not fully involved the things around students and tends to only train students' ability to answer questions. The purpose of this study is to describe the way pottery crafters construct curved-sided spaces and reveal the concept of curved-sided spaces found in pottery making in Banyumulek Village. This type of research is descriptive qualitative research. The subjects in this study were two pottery artisans who were selected using purposive sampling technique. The research subjects were chosen based on certain considerations, namely the subject is a practitioner or expert in making pottery. The data collection techniques used were interviews, observation, and documentation. The results showed that the way pottery craftsmen construct the curved side space in pottery making consists of 4 processes, namely, making tombong (base), bebentet (curved side), belong (neck or connecting curve), and making biwir (mouth or lid) pottery. In addition, there is a concept of curved-sided space in pottery making in Banyumulek Village, namely the concept of partial tubes, cones, spheres, and the concept of whole tubes.